Removable Appliance For Oral Self-Mutilation In Lesch-Nyhan Syndrome. A Case Report - Tahmasbi, Soodeh; Mohamadian, Fatemeh; Tavakol Davani, Shiva; Eftekhar, Leila (Journal of Dental School, 2021)
Objectives Lesch-Nyhan syndrome is a rare inherited disorder associated with self-harming behaviors, delayed mental and motor development, and disturbances such as dysarthria, choreoathetosis, and spasticity. Severe inflicted behaviors in Lesch-Nyhan syndrome often include chewing and biting of the lips or fingers, which often require management. Techniques to deal with these behaviors include using appliances that restrict the behavior or ultimately extracting the teeth. Case This case report presents a 6-year-old child with Lesch-Nyhan syndrome and self-mutilation. He had chronic wounds in his buccal mucosa due to severe biting. Two acrylic devices with anterior and posterior bite plates were designed for the maxillary and mandibular teeth. At the follow-up visits, the wounds had been healed, but due to shedding of the primary teeth, and poor patient cooperation, the appliance design was slightly changed. The design of the device used for the patient inspires similar devices for patients with self-mutilation behaviors. Conclusion Early diagnosis and management of patients suffering from self-injurious behaviors may improve oral health-related quality of life of these patients. Acrylic appliances seem to be effective to minimize injury and to enhance fast healing of oral lesions.